Marketing Strategy and branding approach to achieve customer value in local business - Suryatno Wiganepdo Soegoto; Dedi Sulistiyo Soegoto (JURISMA : Jurnal Riset Bisnis & Manajemen, 2026)
The role of marketing and brand strategy in the business world, both nationally and locally, has implications for the value expected to be received by customers. So we need an empirical analysis of these variables through research methods based on quantitative methods, multiple linear regression analysis. The variables measured were: Marketing Strategy and brand as exogenous variables (X) and customer value as endogenous variables (Y). Objects of research include product shops in Bandung as the unit of analysis. The data collection technique used saturated random sampling with 100 respondents from product shop customers in Bandung. Statistical analysis using classical assumption test and hypothesis testing Z, T and F with a significant level (α) 5% and calculated by statistical analysis. The results showed a significant influence between marketing strategy, brand, on customer value. Marketing strategy and brand variables affect customer value either partially or simultaneously. Keywords: Marketing Strategies; Brand; Customer Value; Retail Business; Bandung